2015
DOI: 10.1007/s00520-015-3004-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an eHealth application “OncoKompas” to improve personalized survivorship cancer care

Abstract: PurposeThe purpose of this study was to investigate the feasibility of an online self-management application (OncoKompas) among cancer survivors. In OncoKompas, cancer survivors can monitor their quality of life (QOL) via participant reported outcomes (PROs) (“Measure”), which is followed by automatically generated individually tailored feedback (“Learn”) and personalized advice on supportive care services (“Act”).MethodsA pretest–posttest design was used, conducting a survey before providing access to OncoKom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(134 citation statements)
references
References 37 publications
4
127
0
3
Order By: Relevance
“…To ensure sustainable usage, Oncokompas is developed following an iterative participatory design [12,23,25,26], meaning that we strive for constant optimization of Oncokompas while involving cancer survivors and healthcare professionals (HCPs) in each step of the development process. First, a needs assessment was conducted among BC and head-and neck cancer (HNC) survivors and HCPs [12,25].…”
Section: Developmental Processmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure sustainable usage, Oncokompas is developed following an iterative participatory design [12,23,25,26], meaning that we strive for constant optimization of Oncokompas while involving cancer survivors and healthcare professionals (HCPs) in each step of the development process. First, a needs assessment was conducted among BC and head-and neck cancer (HNC) survivors and HCPs [12,25].…”
Section: Developmental Processmentioning
confidence: 99%
“…Next, usability of a prototype of Oncokompas was tested by HNC survivors in two iterative cycles and HCPs participated in cognitive walkthroughs [27]. Subsequently, HNC survivors participated in a multi-center study to assess feasibility of this prototype [23]. In response to the results of this feasibility study, Oncokompas was optimized.…”
Section: Developmental Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search was part of a larger systematic review (Prospero ID 42017057237 [14]) investigating the validity of 39 different PROMs measuring quality of life of cancer survivors included in an eHealth application called “Oncokompas” (Amsterdam, the Netherlands) [1518]. The databases Embase, Medline, PsycINFO, and Web of Science were searched for publications that investigated measurement properties of these 39 PROMs including the EORTC IN-PATSAT32.…”
Section: Methodsmentioning
confidence: 99%
“…This result is in line with a study by Ruland et al [49], in which an analysis of use patterns in an eHealth intervention to support cancer patients' illness management revealed that female patients used the system almost twice as often as male patients. However, a study by Duman-Lubberding et al [50] investigated the feasibility of an online self-management application and did not find a gender difference in adherence. Therefore, it seems likely that the type of intervention (e.g.…”
Section: Predictors For Adherencementioning
confidence: 98%